Evaluating under the optical of other professions (a pedagogical experience) (Revista Electrónica REDINE, 2018)
This article determinates the pedagogical experience developed in the evaluation of the learnings of the diploma in university teaching managed by the Libertador Experimental Pedagogical University and Luis Beltran Prieto Figueroa University, during the academic period from March to April 2011. There was a group of 23 professional participants of different  specialties. The purpose was to develop the theoretical and procedural knowledge to sustantiate and  implement the evaluation of the learnings as a creative process inherent to the didactic process in the university education. Praxis generated answer to the explicit intentions in the course program. It itself originated some theoretical   and practical reflections to trace a result that permits to the participants to assume a favorable attitude to the planning, administration and execution of an evaluative process together with enriched actions, humans, warm, emphatic, creative’s and filled of jocosity; all of  these opened a space to a “learning by doing”, learning by sharing, learning both (teachers – participants) coming to do creative productions appropiate to the evaluative fact.
Keywords: evaluative doing; teaching profile